2016
DOI: 10.1007/s10965-016-1092-4
|View full text |Cite
|
Sign up to set email alerts
|

Joule effect self-heating of epoxy composites reinforced with graphitic nanofillers

Abstract: Self-heating of conductive nanofilled resins due to the Joule effect is interesting for numerous applications, including computing, self-reparation, self-post-curing treatment of resins, fabrication of adhesive joints, de-icing coatings and so on. In this work, we study the effect ofthe nature and amount of graphitic nanofiller on the self-heating of epoxy composites.The addition of graphitic nanofillers induced an increase in the thermal conductivity ofthe epoxy resins, directly proportional to the nanofiller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Thermal stability is reduced at ≥0.3 wt % Gr content and the graph shifted toward low temperature in comparison with the epoxy. The improvement in thermal stability of the Gr composite is postulated due to a sheet barrier effect or torturous path effect, which prevents the entry of oxygen and exit of volatile products evolved at high temperature or during thermal degradation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal stability is reduced at ≥0.3 wt % Gr content and the graph shifted toward low temperature in comparison with the epoxy. The improvement in thermal stability of the Gr composite is postulated due to a sheet barrier effect or torturous path effect, which prevents the entry of oxygen and exit of volatile products evolved at high temperature or during thermal degradation …”
Section: Resultsmentioning
confidence: 99%
“…With further increase in filler content, the modulus starts to reduce due to agglomeration. The retention of higher modulus by composites above room temperature, as compared to neat epoxy, is due to the restricted segmental mobility of polymer structure . Storage modulus and elastic modulus are different properties.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Fick's second diffusion law, the diffusivity of water in an epoxy matrix can be obtained from the linear part of W t ~ t 0.5 curve. At the initial stage of absorption, the following equation is arguable : WtWiWmWi=4Dtπh20.25em where w i is the initial weight and w t is the weight at a specific time t , w m is the equilibrium weight, D is the diffusivity, and h is the thickness of the specimen.…”
Section: Resultsmentioning
confidence: 99%
“…From Table , the epoxy composite filled with 0.3 wt% GOSiF has a low diffusivity coefficient of 1.29 × 10 −06 mm 2 /s. The water absorption through epoxy composite is influenced by many aspects, including free volume, cross‐linking degree of the matrix, morphology, hydrophobicity, and so forth . The decreases in the water equilibrium and diffusion coefficient of epoxy composites can be explained by two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…In previous engineering applications, conventional oven heating was mostly used to cure polymer-based composites, but it was often observed that the heat distribution was not uniform, and that a relatively long period of heating was required during manufacturing. Therefore, internal heating methods, such as Joule, microwave, and induction heating, have been of great interest due to their non-contact heating process, which creates uniform thermal distribution and requires only short heating times [ 14 , 15 , 16 , 17 , 18 ]. In particular, Joule heating is one of the most effective ways to provide uniform heating of conductive composites.…”
Section: Introductionmentioning
confidence: 99%